Patterns of attentional bias in antenatal depression: an eye-tracking study - Xu, Yao; Zheng, Peiwen; Feng, Wenqian; Chen, Lipeng; Sun, Shiyu; Liu, Jie; Tang, Weina; Bao, Ciqing; Xu, Ling; Xu, Dongwu; Zhao, Ke (Frontiers in Behavioral Neuroscience, 2023)
One of the most common mental disorders in the perinatal period is depression, which is associated with impaired emotional functioning due to alterations in different cognitive aspects including thought and facial emotion recognition. These functional impairment may affect emerging maternal sensitivity and have lasting consequences for the dyadic relationship. The current study aimed to investigate the impact of depressive symptoms on the attention bias of infant stimuli during 2 This is a provisional file, not the final typeset article pregnancy. Eighty-six pregnant women completed the Edinburgh Postnatal Depression Scale and an eye-tracking task comprising infant-related emotion images. All participants showed biased attention to infant-related images. First, compared to healthy pregnant women, pregnant women with depression symptoms initially directed their attention to infant-related stimuli more quickly (F (1, 84) = 6.175, P = 0.015, η² = 0.068). Second, the two groups of pregnant women paid attention to the positive infant stimuli faster than the neutral infant stimuli, and the first fixation latency bias score was significantly smaller than that of the infant-related negative stimulus (P = 0.007). Third, compared with the neutral stimulus, the non-depression group showed a longer first gaze duration to the negative stimulus of infants (P = 0.019), while the depressive symptoms group did not show this difference. We speculate that structural and functional changes in affective motivation and cognitiveattention brain areas may induce these attentional bias patterns. These results provide suggestions for the implementation of clinical intervention programs to correct the attention bias of antenatal depressed women.